Governance Mechanisms and Ownership in an Emerging Market: The Case of Turkish Banks - Bektas, Eralp; Kaymak, Turhan (Routledge Journals, Taylor & Francis Ltd, 2009)
This study investigates the relations of board structure, ownership concentration, and ownership type with the performance of banks operating in Turkey from an agency theory and resource-dependency perspective. We use financial ratios and established measures of board characteristics and ownership structure. Our results indicate that board size and duality do not significantly influence the returns on assets of Turkish banks. On the other hand, the tenure of board members is negatively related to performance. Our analysis of board composition reveals a curvilinear relationship with banks' performance, implying that boards composed of a majority of either insiders or outsiders enjoy high performance. Also, ownership concentration and ownership type do not influence firm performance. The results of the financial variables are robust in all models.
Keywords: bank performance; board characteristics; corporate governance; ownership